CITRA PEREMPUAN DALAM NOVEL ISLAMMU ADALAH MAHARKU KARYA ARIO MUHAMMAD - Annisa, Ria; Zulfitriyani, Zulfitriyani; Samsiarni, Samsiarni (Universitas Tanjungpura, 2026)
Abstract This study aims to describe the self-image and social image of women. Qualitative research with a descriptive analysis method is used in this study. The data source in this study is the novel Islammu is Maharku by Ario Muhammad, the seventh edition in 2020. Data collection was carried out by reading, marking, recording, and inventorying data. For data accuracy using triangulation techniques. Data analysis was carried out by data reduction, data presentation and drawing conclusions. This study produces self-image and social image of women. The self-image of women from the physical aspect is adult women, beautiful and women dressed modestly. The image of women from the psychological aspect is women who think and feel, are intelligent and assertive. The social image of women depicted is women in the family as a mother and child. In the community, the social image depicted is women as young lecturers, postgraduate students, lab members. This research can be applied in Indonesian language learning in grade XII even semester, namely in KD 3.9 analyzing the content and language of novels and KD 4.9 designing novels or novelettes by paying attention to the content and language. Keywords: Image of Woman, novel, Islammu adalah Maharku Abstrak Penelitian ini bertujuan untuk mendeskripsikan citra diri dan citra sosial perempuan. Penelitian kualitatif dengan metode deskriptif analisis digunakan dalam penelitian ini. Sumber data dalam penelitian ini yaitu novel Islammu adalah Maharku karya Ario Muhammad, cetakan ketujuh pada tahun 2020. Pengumpulan data dilakukan dengan cara membaca, menandai, mencatat, dan menginventarisasi data. Untuk keakuratan data menggunakan teknik triangulasi. Analisis data dilakukan dengan reduksi data, penyajian data dan menarik kesimpulan. Penelitian ini menghasilkan citra diri dan citra sosial perempuan. Citra diri perempuan dari aspek fisik yaitu perempuan dewasa, cantik dan perempuan berpakaian tertutup. Citra perempuan dari aspek psikis yaitu perempuan berpikir dan berperasaan, cerdas dan tegas. Citra sosial perempuan yang tergambar yaitu perempuan dalam keluarga sebagai seorang ibu dan anak. Di lingkungan masyarakat citra sosial yang tergambar yaitu perempuan sebagai dosen muda, mahasiswa S2, anggota lab. Penelitian ini dapat diaplikasikan dalam pembelajaran Bahasa Indonesia pada kelas XII semester genap yaitu pada KD 3.9 menganalisis isi dan kebahasaan novel dan KD 4.9 merancang novel atau novelet dengan memerhatikan isi dan kebahasaan. Kata Kunci: Citra perempuan; Novel; Islammu adalah Maharku